Overcoming Structural Barriers in Shrimp Downstreaming: Toward Sustainable Aquaculture in Sumbawa Island - Yasir Arafat; Mustaqim; Irfan Thofiq Firdaus; Lalu Suhaimi; Alfie Fahruz Zubaidah; Rully Puji Agung (Pusbindiklatren Bappenas, 2025)
This study aims to identify the structural barriers of shrimp downstreaming in Sumbawa Island, Indonesia, from a sustainable aquaculture perspective, highlighting its significance for the environment, economic diversification, and social inclusivity. A mixed-methods approach was employed, combining a Systematic Literature Review (SLR) of scientific articles and policy documents with two Focus Group Discussions (FGDs) involving 35 participants, and field observations. These data sources were integrated through thematic policy analysis to triangulate insights from literature, lived experience, and empirical realities. The findings reveal that in 2023, Sumbawa accounted for 71.51% of NTB’s shrimp production and 14.78% of national output, equivalent to 139,201 tons. Despite its substantial contribution, the downstream sector remains underdeveloped due to limited cold storage, low adoption of advanced technology, and weak cooperative institutions. Realizing Sumbawa’s potential as a regional hub requires coordinated infrastructure investment, institutional strengthening, and an integrated roadmap with spatial planning that embeds sustainable aquaculture principles. Addressing these structural gaps will not only enhance competitiveness in domestic and export markets but also generate more inclusive benefits for coastal communities, thereby advancing sustainable territorial development.